Assessing the relationship between risk assessment practices, risk control practices, quality risk management and construction project performance: an empirical study in Malaysian construction industry / Affiaine Ahmad - Ahmad, Affiaine (Institute of Graduate Studies, UiTM, 2014)
This study focuses on the relationship between the risk assessment practices (RAP), risk control practices (RCP), quality risk management (QRM) and construction project performance (CPP). This study is basically a measurement centers around the implementation of the project risk management (PRM) that includes the processes concerned with identifying, analyzing, and responding to project risk. Survey data gathered from 264 projects in G7 grade of contractors in Malaysia was used to assessing the relationships between the stated variables. The analysis were performed using rigorous statistical analysis of SPSS version 16 and AMOS program for structural equation modeling (SEM) techniques. Results show that RAP is observed to have a positive relationship on QRM, but no direct relationship on CPP. RCP has direct positive relationship to both QRM and CPP. Whereas QRM has a positive relationship on CPP.